Runaway Social Selection in Human Evolution - Crespi, Bernard J.; Flinn, Mark V.; Summers, Kyle (Frontiers in Ecology and Evolution, 2022)
Darwin (1871) posited that social competition among conspecifics could be a powerful selective pressure. Alexander (1990) proposed a model of human evolution involving a runaway process of social competition based on Darwin’s insight. Here we briefly review Alexander’s logic, and then expand upon his model by elucidating six core arenas of social selection that involve runaway processes, and that were likely involved in the evolution of the remarkable combination of adaptations in humans. We hypothesize that the key life history innovation that opened the door to runaway social selection and cumulative culture was increased cooperation among individuals in small fission-fusion groups.